Unveiling the antioxidant and anti-inflammatory potential of syringic acid: mechanistic insights and pathway interactions - Zhao, Zhejun; Yang, Qiuhua; Sun, Yuanlong; Ruan, Xiaofen (Frontiers in Pharmacology, 2025)
BackgroundSyringic acid (SA), a naturally occurring phenolic acid, has garnered significant attention for its antioxidant and anti-inflammatory properties. However, the mechanisms underlying these effects and their potential therapeutic applications require further elucidation.MethodsA comprehensive literature review was conducted using PubMed and Web of Science (1965–2024) to investigate the antioxidant and anti-inflammatory mechanisms of SA, with a focus on oxidative stress and inflammatory pathways. For insights related to traditional Chinese medicine (TCM), we referenced Chinese literature. Articles focusing on agriculture, industry, and economics are excluded.ResultsSA exerts potent antioxidant and anti-inflammatory activities through multiple mechanisms. Specifically, it mitigates OS by scavenging free radicals, enhancing endogenous antioxidant defenses, and activating the KEAP1/NRF2 pathway. It also inhibits inflammation by downregulating key mediators, including NF-κB, TLR4, HMGB1, MyD88, and TRAF6. Crosstalk between NRF2, NF-κB, and PI3K/AKT pathways reveals SA’s involvement in cellular pathophysiological processes such as apoptosis, ferroptosis, and endoplasmic reticulum stress.ConclusionSA’s robust antioxidant and anti-inflammatory mechanisms underscore its promise as a therapeutic agent. Future research should address its pharmacokinetics, safety profile, and clinical potential.